2022
DOI: 10.1002/cnma.202200349
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Polycationic Silver Nanocluster‐Impregnated PLGA Nanocomposites with Potent Antimicrobial Activity

Abstract: Ultrasmall cationic silver nanoparticles (AgNPs) have recently emerged as highly potent antimicrobial agents for the treatment of multidrug‐resistant bacteria and their biofilms. However, the clinical application of these cationic AgNPs is hampered by their poor stability and high reactivity in solution, leading to uncontrolled release of toxic silver ions. An ideal platform featuring broad‐spectrum antibacterial activity and high biocompatibility that prevents overexposure to silver ions, is therefore highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The increased susceptibility of P. aeruginosa and S. aureus biofilms accounts for potent antibiofilm capacity of ultrasmall AgNPs that can accumulate within biofilm structure facilitating structural damage and enhanced bacterial penetration. 14,21 We have previously shown that the small sized AgNPs can overcome single species biofilm structural barrier with favourable uptake resulting in biofilm disintegration, against both Gram-negative and -positive bacteria using clinically relevant in vitro and preclinical animal infection wound models where their application was safe and no adverse effects were observed. 14,21 Nanoparticle's size dependent antibacterial effect of silver has also been studied using mesoporous silica nanoparticles, 22 biofilm responsive nanoantibiotic containing small sized AgNPs 23 and surface coated ultrasmall AgNPs to boost antibacterial efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased susceptibility of P. aeruginosa and S. aureus biofilms accounts for potent antibiofilm capacity of ultrasmall AgNPs that can accumulate within biofilm structure facilitating structural damage and enhanced bacterial penetration. 14,21 We have previously shown that the small sized AgNPs can overcome single species biofilm structural barrier with favourable uptake resulting in biofilm disintegration, against both Gram-negative and -positive bacteria using clinically relevant in vitro and preclinical animal infection wound models where their application was safe and no adverse effects were observed. 14,21 Nanoparticle's size dependent antibacterial effect of silver has also been studied using mesoporous silica nanoparticles, 22 biofilm responsive nanoantibiotic containing small sized AgNPs 23 and surface coated ultrasmall AgNPs to boost antibacterial efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…14,21 We have previously shown that the small sized AgNPs can overcome single species biofilm structural barrier with favourable uptake resulting in biofilm disintegration, against both Gram-negative and -positive bacteria using clinically relevant in vitro and preclinical animal infection wound models where their application was safe and no adverse effects were observed. 14,21 Nanoparticle's size dependent antibacterial effect of silver has also been studied using mesoporous silica nanoparticles, 22 biofilm responsive nanoantibiotic containing small sized AgNPs 23 and surface coated ultrasmall AgNPs to boost antibacterial efficacy. 24 It is noteworthy that ultrasmall size AgNPs are highly susceptible to fast oxidation and dissolution, facilitating fast leaching of silver ions and short antibacterial duration with associated potential toxicity.…”
Section: Introductionmentioning
confidence: 99%